2022
DOI: 10.21203/rs.3.rs-1632405/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative Visual Performance of Diffractive Bifocal and Rotationally Asymmetric Refractive Intraocular Lenses

Abstract: We compared the visual performance of a diffractive bifocal intraocular lens (IOL) with +4.0 D near addition (ZMB00 [Johnson & Johnson Surgical Vision]) and a rotationally asymmetric refractive IOL with +1.5 D near addition (LS-313 MF15 [Teleon Surgical BV]) 10 weeks after cataract patients’ last surgery for bilateral ZMB00 or LS-313 MF15 implantation, with the lenses of each eye implanted within 3 months of each other. The ZMB00 and LS-313 MF15 groups comprised 1326 eyes of 663 patients (age: 67.0±7.8 yea… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(19 citation statements)
references
References 7 publications
(11 reference statements)
0
19
0
Order By: Relevance
“…The study showed that patients in the monofocal group had better contrast sensitivity and higher night driving scores. As in the previous studies 17,18 , we used the CGT-1000 instrument to measure contrast sensitivity; this device determines the contrast threshold with an automated strategy for 6 spatial frequencies 19,20 . In this study, the contrast sensitivity with glare was signi cantly better in the rotationally asymmetric refractive group at 6.3 degrees.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study showed that patients in the monofocal group had better contrast sensitivity and higher night driving scores. As in the previous studies 17,18 , we used the CGT-1000 instrument to measure contrast sensitivity; this device determines the contrast threshold with an automated strategy for 6 spatial frequencies 19,20 . In this study, the contrast sensitivity with glare was signi cantly better in the rotationally asymmetric refractive group at 6.3 degrees.…”
Section: Discussionmentioning
confidence: 99%
“…The results of multiple regression analysis for all postoperative parameters, which were adjusted by multiple regression with the explanatory variables in Table 1 in the same way as in our previous study 17,18 , for the monofocal and rotationally asymmetric refractive groups 10 weeks after surgery on both eyes are shown in Supplementary Table S2. Corrected distance visual acuity and the higher-order aberrations (ocular/internal, scaled to a pupil size of 4 mm/6 mm) WF_4_post_O_TotalHOA, _Third, _Fourth, _Trefoil, _Coma, _Tetrafoil, _Spherical, WF_4_post_I_TotalHOA, _Third, _Fourth, _Trefoil, _Coma, _Tetrafoil, _Spherical, WF_6_post_O_Spherical, and WF_6_post_I_Spherical were signi cantly better in the monofocal group (p < 0.00068, Wald test) (Table 2 and Fig.…”
Section: Comparison Of Postoperative Parameters Between Tecnis Monofo...mentioning
confidence: 99%
See 1 more Smart Citation
“…Preoperatively, all patients received full ophthalmologic examinations, including evaluations of the corneal curvature radius, corneal astigmatism, axial length, refractive status, ocular aberrations, pupil diameter, distance/intermediate/near visual acuity, contrast sensitivity, and contrast sensitivity under glare, as well as anterior segment evaluations using a slit lamp, tonometry, and indirect fundoscopy, in the same way described in our previous study 11,12 . The quality of vision was evaluated using the Japanese version of the NEI VFQ-25 34 .…”
Section: Preoperative Examinationmentioning
confidence: 99%
“…As in our previous study 11,12 Both groups were adjusted for age, sex, axial length, subjective refraction spherical equivalent, subjective refraction cylinder, corneal astigmatism, corneal higher-order aberrations, and pupil diameter. In the regression analyses (2) and (3), the data were divided into two parts (left-eye data and right-eye data), and the regression model was applied to each dataset.…”
Section: Statistical Analysesmentioning
confidence: 99%